2011
DOI: 10.1016/j.placenta.2010.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Review: Oxygen and trophoblast biology – A source of controversy

Abstract: Oxygen is necessary for life yet too much or too little oxygen is toxic to cells. The oxygen tension in the maternal plasma bathing placental villi is <20 mm Hg until 10–12 weeks’ gestation, rising to 40–80 mmHg and remaining in this range throughout the second and third trimesters. Maldevelopment of the maternal spiral arteries in the first trimester predisposes to placental dysfunction and sub-optimal pregnancy outcomes in the second half of pregnancy. Although low oxygen at the site of early placental devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
131
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(134 citation statements)
references
References 79 publications
(101 reference statements)
2
131
1
Order By: Relevance
“…A number of reports have demonstrated that trophoblast cells respond to oxygen restriction (reviewed in ref. 34). In vitro experimentation has yielded a range of responses, some of which are contradictory, but, again, methodological differences are the likely cause for the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have demonstrated that trophoblast cells respond to oxygen restriction (reviewed in ref. 34). In vitro experimentation has yielded a range of responses, some of which are contradictory, but, again, methodological differences are the likely cause for the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 In contrast, increased trophoblastic apoptosis has been reported in pregnancies complicated by fetal growth restriction (FGR) or preeclampsia (PE), [3][4][5] suggesting that altered regulation of trophoblastic apoptosis may contribute to the pathophysiology of FGR or PE. 6 Autophagy has been implicated in pathophysiologic processes including cellular differentiation, cancer, metabolic or neurodegenerative diseases, and cell death. 7,8 However, autophagic function in the human placenta is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In the first trimester, placental O 2 levels are relatively low, with a pressure around 20 mmHg (Tuuli et al 2011), due to lack of established maternal intraplacental circulation, which is believed to be the reason why the embryo is particularly protected from ROS at that time. These low O 2 levels are essential for normal cell proliferation and placental angiogenesis, promoted by hypoxia-induced transcriptional and posttranscriptional regulation of angiogenic factors such as vascular endothelial growth factor and placental growth factor (Tuuli et al 2011). However, once maternal intraplacental circulation is fully established (toward the end of the first trimester), the O 2 tension triples and, with it, so does ROS levels, particularly at the syncytiotrophoblastic layer (Burton and Jauniaux 2011;Burton et al 2010).…”
mentioning
confidence: 99%
“…However, once maternal intraplacental circulation is fully established (toward the end of the first trimester), the O 2 tension triples and, with it, so does ROS levels, particularly at the syncytiotrophoblastic layer (Burton and Jauniaux 2011;Burton et al 2010). The placenta then adapts to this increase by modulating hypoxia-inducible factor 1α (HIF-1α) and increasing cellular antioxidant levels (Tuuli et al 2011). Under normal conditions, this adaptation is favorable to fetal development.…”
mentioning
confidence: 99%
See 1 more Smart Citation